المسائل التي خالف فيها المالكية أصل مذهبهم في التوريث - العرفي, كمال (جامعة الوادي - University of Eloued, 2021)
الأصل في مذهب الإمام مالك انبناؤه في أحكام المواريث على قول سيدنا زيد بن ثابت رضي الله عنه، وهو شأن المذهبين الشافعي والحنبلي أيضا، ولم يخالف الفقه المالكي هذا الأصل إلا في ثلاث مسائل هي : المالكية وشبه المالكية، وكلاهما من المسائل الشاذة، والثالثة توريث أم الجد. ويهدف هذا المقال إلى بيان أسس هذه المخالفة، من حيث مأخذها وتعليلها وحججها، ومحاولة الوقوف على التسبيب والتأصيل المتصلين بها. وقد توصل البحث إلى أن المخالفة في هذه المسائل مبناها على النظر الفقهي، ورافقها تعليل متميز، وكذا نظرة مبتكرة في إعمال القواعد، وتخريج الأحكام، وبخاصة في المسألتين الأوليين، بما يمكن أن يتيح مجالا أرحب في معالجة النوازل والمستجدات، وفقا لملكة منفتحة على اعتماد المحاورة الذهنية العلمية المعتمدة على استعمال أمثل للتأصيل والتأسيس والتخريج وفاقا لمزاوجة متوازنة بين اعتماد النصوص وحسن فهمها والاستنباط منها، وإعمال القياس والأدلة العقلية خدمة لإبراز أفضل لصورة الأحكام الشرعية. The origin of Imam Malik’s doctrine that it is based on the rulings of inheritance according to the saying of our master Zaid bin Thabit, may God be pleased with him, and it is the case of the Shafi’i and Hanbali schools as well, and the Maliki jurisprudence did not violate this principle except in three issues: the Malikis and the semi-Maalikis, both of which are abnormal issues, and the third is the inheritance of a mother Grandpa. This article aims to clarify the foundations of this violation, in terms of its sources, justifications and arguments, and an attempt to identify the causation and rooting related to it. The research concluded that the violation in these issues is based on jurisprudential consideration, accompanied by a distinct reasoning, as well as an innovative view in the implementation of the rules, and the graduation of provisions, especially in the first two
Issues in which the Malikis disagreed with the Origin of their Doctrine of Inheritance
مقال
Keywords: المسائل؛ المالكية؛ الأصل؛ المذهب؛ المخالفة; Maliki; origin; denomination; offense